Antinociceptive effects and mechanisms of action of Clinacanthus nutans Lindau leaf methanolic and petroleum ether extracts in mice - Abdul Rahim, Mohammad Hafiz (2017)
Clinacanthus nutans (C. nutans) Lindau is a shrub widely cultivated in the South East Asian region including Malaysia. It has traditionally been used for the treatment of various ailments including pain–mediated diseases. Although various pharmacological activities of this plant have been reported, its pain–relieving activity has been neglected. Therefore, the objective of the present study is to determine the chemical constituents, acute and subchronic toxicity, and antinociceptive effects of the C. nutans leaf extracts. Phytochemical screening and chromatography methods analysis, i.e., High Performance Liquid Chromatography (HPLC), Ultra High Performance Liquid Chromatography–Electrospray Ionisation (UHPLC–ESI) and Gas Chromatography–Mass Spectrometry (GC–MS), standard procedures were carried out to determine the presence of bioactive compounds. Acute (14 days) and subchronic (28 days) oral toxicity tests were performed according to the Organisation for Economic Co–operation and Development (OECD) guidelines. The antinociceptive effect of C. nutans leaf methanol extract (MECN) was investigated using acetic acid–induced abdominal constriction, hot plate, and formalin–induced paw licking tests. The antinociceptive effects of its partitions, i.e., petroleum ether (PECN), ethyl acetate (EACN), and aqueous (AQCN) partitions, were evaluated using acid–induced abdominal constriction test. The PECN, which was the most effective in acetic acid–induced abdominal constriction test, was further subjected to hot plate and formalin–induced paw licking tests. Furthermore, the MECN and PECN also were subjected to the rota–rod test in order to determine non–specific sedative effects. The roles of capsaicin, glutamate, phorbol 12–myristate 13–acetate (PMA), bradykinin, various non–opioid and opioid receptors, L–arginine–nitric oxide (NO)–cyclic Guanosine Monophosphate (cGMP) and potassium (K+) channels pathway in MECN and PECN–induced antinociception were also evaluated. Phytochemical Screening of MECN and PECN revealed the presence of flavonoids, saponins, steroids and triterpenes. Further analysis, i.e., HPLC, UHPLC–ESI, and GC–MS, of the extracts have revealed the presence of polyphenolic compounds such as phenolic acid and flavonoid–based compounds as major components. In the acute toxicity test, the median lethal dose (LD50) estimated for C. nutans leaf was more than 5000 mg/kg body weight, whereas in subchronic toxicity test, the no–observed–adverse–effect levels (NOAELs) estimated was more than 2500 mg/kg body weight/day. Oral administration of 100, 250, and 500 mg/kg body weight MECN and PECN produced significant (p < 0.05) inhibition in acetic acid–, formalin–, capsaicin–, glutamate–, PMA–, bradykinin–induced nociception, while in hot plate test, only the highest dose showed significant (p < 0.05) pain inhibition. In the rota–rod test, 500 mg/kg body weight extracts did not show any significant (p> 0.05) effect on motor coordination. The antinociceptive activity of 500 mg/kg body weight extracts were significantly (p< 0.05) reversed by pre–treatment with L–arginine, while PECN but not MECN significantly (p < 0.05) reversed by pre–treatment with 1H–[1,2,4]oxadiazole[4,3–a]quinoxaline–1–one (ODQ). The present study also showed that 500 mg/kg body weight MECN and PECN produced significant (p < 0.05) antagonised following pre–treatment with non–opioid and opioid receptor antagonists, i.e., yohimbine, pindolol, caffeine, haloperidol, atropine, β–funaltrexamine, naltrindole, and nor–binaltorphimine, and various K+ channels blockers, i.e., glibenclamide, apamin, charybdotoxin and tetraethylammonium chloride. In conclusion, MECN and PECN exert antinociceptive activity at both central and peripheral pain pathways through the modulation of the vanilloidergic, glutamatergic, bradykininergic, noradrenergic, serotonergic, adenosinergic, dopaminergic, cholinergic, and opioidergic receptors, protein kinase C, NO–cGMP–independent or dependent, and K+ channels pathways systems. The synergistic actions of the bioactive compounds contribute to the antinociceptive activity of MECN and PECN.